Penerapan Algoritma Apriori Terhadap Data Penjualan Pada Online Shop (Studi Kasus: Afandi Grosir Account) - Qudury, Abil (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
Opening an online business is one way to increase income for many people. Buying and selling online is becoming more competitive as the number of olshops is increasing day by day. This makes some online business owners frustrated because their products are not selling well, there are no buyers, or confused with product additions and promotional strategies. However, this situation does not affect the increase in people shopping online. Afandi Grosir Account is no exception, sales of mobile phone accessories at the shopee olshop Afandi Grosir Account are sold unevenly so that there are items that sell and not sell, that's what causes Afandi Grosir Accounts to have problems with restocking and promotion/marketing strategies to increase product sales. This a priori algorithm can be used in the sales process, by providing a relationship to sales data, so that consumer buying patterns will be obtained. Based on the test results, the final result of the association rules formed, both using manual calculations and testing using WEKA tools using the a priori algorithm with a minimum value of 60% support and 80% confidence, produces 18 association rules that are similar to the lift ratio ≥ 1, so the association rules are sufficient. valid if you want to be used as a solution or alternative reference for decision making.